XRCC1-DNA polymerase beta interaction is required for efficient base excision repair. - Dianova, I; Sleeth, K; Allinson, S; Parsons, J; Breslin, C; Caldecott, K; Dianov, G (2004)
X-ray repair cross-complementing protein-1 (XRCC1)-deficient cells are sensitive to DNA damaging agents and have delayed processing of DNA base lesions. In support of its role in base excision repair, it was found that XRCC1 forms a tight complex with DNA ligase IIIalpha and also interacts with DNA polymerase beta (Pol beta) and other base excision repair (BER) proteins. We have isolated wild-type XRCC1-DNA ligase IIIalpha heterodimer and mutated XRCC1-DNA ligase IIIalpha complex that does not interact with Pol beta and tested their activities in BER reconstituted with human purified proteins. We find that a point mutation in the XRCC1 protein which disrupts functional interaction with Pol beta, affected the ligation efficiency of the mutant XRCC1-DNA ligase IIIalpha heterodimer in reconstituted BER reactions. We also compared sensitivity to hydrogen peroxide between wild-type CHO-9 cells, XRCC1-deficient EM-C11 cells and EM-C11 cells transfected with empty plasmid vector or with plasmid vector carrying wild-type or mutant XRCC1 gene and find that the plasmid encoding XRCC1 protein, that does not interact with Pol beta has reduced ability to rescue the hydrogen peroxide sensitivity of XRCC1- deficient cells. These data suggest an important role for the XRCC1-Pol beta interaction for coordinating the efficiency of the BER process.